On microservices, bounded contexts, and everything in between (O'Reilly Media, 2019)
"Vladik Khononov (Invesus Group) explains how to decompose a system into loosely coupled components: how to draw boundaries between services, how to decide whether some logic belongs to one service or another, and how domain-driven design can help us make those decisions. Finally, he takes a stab at answering the age-old question of what part of a microservice should be "micro" and how it can be measured. You'll hear about neither Docker nor Kubernetes. Actually, nothing related to infrastructure. Instead, you'll dive into the difference between microservices and bounded contexts, discover when each pattern should be used, and get takeaways from Vladik's experience optimizing microservices--quote based architectures at Naxex. This session was recorded at the 2019 O'Reilly Software Architecture Conference in San Jose."--Resource description page